Elevated CO2 and warming shift the functional composition of soil nematode communities in a semiarid grassland. (December 2016) - Mueller, Kevin E.; Blumenthal, Dana M.; Carrillo, Yolima; Cesarz, Simone; Ciobanu, Marcel; Hines, Jes; Pabst, Susann; Pendall, Elise; de Tomasel, Cecilia Milano; Wall, Diana H.; Eisenhauer, Nico
Abstract: Climate change can alter soil communities and functions, but the consequences are uncertain for most ecosystems. We assessed the impacts of climate change on soil nematodes in a semiarid grassland using a 7-year, factorial manipulation of temperature and [CO2 ]. Elevated CO2 and warming decreased the abundance of plant-feeding nematodes and nematodes with intermediate to high values on the colonizer-persister scale (cp3-5), including predators and omnivores. Thus, under futuristic climate conditions, nematode communities were even more dominated by r- strategists (cp1-2) that feed on bacteria and fungi. These results indicate that climate change could alter soil functioning in semiarid grasslands. For example, the lower abundance of plant-feeding nematodes could facilitate positive effects of elevated CO2 and warming on plant productivity. The effects of elevated CO2 and warming on nematode functional composition were typically less than additive, highlighting the need for multi-factor studies. Highlights: We sampled nematodes in a grassland soil after a 7-year CO2  × warming experiment. Elevated CO2 and warming both caused shifts in nematode functional composition. Abundance of plant-feeders, predators and omnivores was reduced by CO2 and warming. Elevated CO2 and warming increased the relative abundance of r -selected nematodes. Effects of elevated CO2 and warming tended to be less than additive (interactive).